2018
DOI: 10.1001/jamaoto.2018.1381
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Tranexamic Acid for Treatment of Bleeding, Edema, and Ecchymosis in Patients Undergoing Rhinoplasty

Abstract: Current available evidence suggests that preoperative administration of tranexamic acid is safe and may reduce intraoperative bleeding as well as postoperative eyelid edema and ecchymosis in patients undergoing rhinoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 73 publications
1
40
0
Order By: Relevance
“…The major clinical benefits of TXA use in plastic surgery are generally the same as in other surgical subspecialties; reduced blood loss and, possibly, hematoma formation. However, the gained anti-inflammatory benefit adds significant appeal for plastic surgeons, especially for cosmetic procedures [9,75]. Given the limited number of clinical studies, additional prospective trials are warranted to study these effects.…”
Section: Discussionmentioning
confidence: 99%
“…The major clinical benefits of TXA use in plastic surgery are generally the same as in other surgical subspecialties; reduced blood loss and, possibly, hematoma formation. However, the gained anti-inflammatory benefit adds significant appeal for plastic surgeons, especially for cosmetic procedures [9,75]. Given the limited number of clinical studies, additional prospective trials are warranted to study these effects.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Conducting a systematic review in 2018, De Vasconcellos et al investigated the effect of TA on the amount of BL during rhinoplasty surgery and according to the results of this study, BL during surgery in the TA-receiving group was significantly less than the control group, which is consistent with the results of the present study. [10] In a study conducted by Kalkarni et al in 2016 on 240 patients undergoing head and neck cancer surgeries, one group of patients was injected with 10 cc/kg of diluted TA before surgery and the other group was injected with the same amount of normal saline. According to the results, there was no significant difference between the two groups in terms of BL during surgery, but there was a significant difference between the TA-receiving group and the control group regarding the amount of BL over 24 h after surgery, both results inconsistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradictory results and most studies that investigated (adeno)tonsillectomy were performed before 1980, and future well-designed randomized controlled trials may shed new light on the findings. For rhinoplasty, a meta-analysis including 276 patients indicated that TXA, 10 mg/kg intravenous or 1 g orally prior to surgery, possibly followed by 1 g 3x/day postoperatively for a maximum of 5 days (Table 1 ), resulted in a significant reduction of intraoperative bleeding (as well as postoperative eyelid edema and ecchymosis) [ 46 ]. There are no data available regarding the thromboembolic events [ 46 ].…”
Section: Maintextmentioning
confidence: 99%
“…For rhinoplasty, a meta-analysis including 276 patients indicated that TXA, 10 mg/kg intravenous or 1 g orally prior to surgery, possibly followed by 1 g 3x/day postoperatively for a maximum of 5 days (Table 1 ), resulted in a significant reduction of intraoperative bleeding (as well as postoperative eyelid edema and ecchymosis) [ 46 ]. There are no data available regarding the thromboembolic events [ 46 ].…”
Section: Maintextmentioning
confidence: 99%